Ameloblastic Carcinoma with Calcification: A Rare Case Report in the Mandible and Literature Review - Neda Kardouni Khoozestani; Farzaneh Mosavat; Mohammad Shirkhoda; Ramtin Azar (Hindawi Limited, 2020)
Ameloblastic carcinoma (AC) is a scarce malignant tumor which is more prevalent in the mandible than the maxilla. It occurs in a wide range of age groups, and there is a sex predilection in males. AC shows specific microscopic features and requires more aggressive surgical treatment plans in comparison with conventional ameloblastoma. Radiographically, AC resembles ameloblastoma except that it rarely represents focal mineralized materials, seemingly reflecting dystrophic calcification. This characteristic is uncommon in typical ameloblastomas, and only few cases reported with such opacities and mineralized materials. Due to this rare radiographic and microscopic presentation, an accurate diagnosis could be challenging, and pathologists should consider a combination of benign and malignant odontogenic tumors occurring in jaws.